Business Process Reengineering Pada PT Cahaya Mega Grup Tour Travel - Sri Juniyanti; Ilyas Nuryasin; Wildan Suharso (Jurnal Repositor, 2023)
Business process is an activity that aims to improve the relationship between business processes in an organization and technical. PT Cahaya Mega Grup Tour Travel has processes to manage and support the goals, vision and mission of the organization in providing services to bookings made by consumers. However, in some services such as plane tickets, travel cars, and tours, there are still manual and time-consuming processes so that there are some business processes whose effectiveness and efficiency are still lacking. So it is necessary to reanalyze business processes that have been running in depth and radical changes must be made. With a Business Process Reengineering (BPR) approach to reengineering and using throughput efficiency tests in calculating efficiency in business processes, and using the standards of the American Society of Machanical Engineers (ASME) in conducting business process analysis. In the initial research at PT Cahaya Mega Grup Tour Travel, it was found that 4 legacy business processes that have been running, this legacy business process has a throughput efficiency of 72%, 69%, 47%, 100% then a business process reengineering is carried out which results in a recommended business process with a throughput efficiency test value of 100%, 100%, 100%, 100% of course with an increase in time in each business process. And from the results of the business process recommendations, it produced a prototype as a reference for making the website of PT Cahaya Mega Grup Tour Travel.